Translation, cross-cultural adaptation, reliability, and validation of the italian version of the Foot and Ankle Disability Index (FADI) - Leigheb, Massimiliano; Rava, Emanuele; Vaiuso, Dario; Samaila, Elena Manuela; Pogliacomi, Francesco; Bosetti, Michela; Grassi, Federico Alberto; Sabbatini, Maurizio (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim of the work: Foot-and-Ankle-Disability-Index (FADI) is one of the mostwidely used evaluation questionnaires for this anatomical district, but an italian validated version lacks and isnecessary to properly evaluate italian people. In fact a correct interpretation of the items by patients is essentialto obtain a precise subjective response, making the questionnaire valid to evaluate patients’ satisfaction andwellness. Our purpose was to translate and culturally adapt into Italian the FADI questionnaire, and to checkits reproducibility and validity. Materials and Methods: The original english version of FADI questionnairewas translated into Italian and checked for medical part coherence. It was submitted to 10 italian randomizedpatients to verify a correct cultural adaptation, and then to other 50 randomized patients operated at theirankle or hallux to assess intra- and inter-observer reproducibility by the Pearson’s-Correlation-Coefficient(PCC) and the Intra-Class-Correlation (ICC) coefficient. Moreover, Short-Form-36 (SF36) questionnairefor Quality-of-Life and Visual-Analogue-Scale (VAS) for pain were also administered to the same 60 peopleand compared to italian-FADI to perform validation analysis by PCC and ICC coefficient. Results: Culturaladaptation of the translated version of the scale resulted good in terms of understandability by patients. Anoptimal correlation of the inter- and intra-observer reproducibility was obtained. The correlation obtainedbetween FADI and SF-36 as well as between FADI and VAS indicates success in the validation process.Conclusions: Validation of the FADI italian version has been performed successfully, its use can be consideredappropriate and is indicated in italian clinical practice. (www.actabiomedica.it)